The Practice of Contemplation in the Work of Gurdjieff. (1st December 2015) - Azize, Joseph
Abstract : In Beelzebub's Tales to his Grandson, Gurdjieff writes of the critical importance of "Aiëssirittoorassnian-contemplation" for the formation of the "soul". First, I discuss some definitions of "meditation" and "contemplation" in relation to Gurdjieff's practices with a view to determining the most appropriate term. Second, commencing with Beelzebub, but ranging across Gurdjieff's oeuvre, I explore his understanding of the "soul", and "Aiëssirittoorassnian-contemplation". I then examine Gurdjieff's first recorded contemplative technique, the "I Am" exercise, thus illuminating an under-appreciated aspect of Gurdjieff's practice. It transpires that Gurdjieff's contemplative techniques are more significant to his practical teaching than previously suspected.